Functionality and Neurocognition in Patients With Bipolar Disorder After a Physical-Exercise Program (FINEXT-BD Study): Protocol of a Randomized Interventionist Program - García, Saínza; Gorostegi-Anduaga, Ilargi; García-Corres, Edurne; Maldonado-Martín, Sara; MacDowell, Karina S.; Bermúdez-Ampudia, Cristina; Apodaca, María J.; Pérez-Landaluce, Irene; Tobalina-Larrea, Ignacio; Leza, Juan C.; González-Pinto, A. (Frontiers in Psychiatry, 2020)
Introduction: Recent studies have shown that symptoms of psychiatric illness, functionality, and cognitive function improve with exercise. The aim of this study will be to investigate whether the implementation of an individualized physical exercise program will improve the functional and neuropsychological status of patients with bipolar disorder (BD). Methods: This longitudinal, interventional, randomized, controlled, simple-blind clinical trial will include 80 patients aged 18-65 years, all of them with BD diagnosis. Patients will be randomly assigned to a physical exercise intervention + Treatment-As-Usual (TAU) group and a non-intervention + TAU group. Patients will be assessed by an extensive battery of clinical tests, physical parameters (e.g. brain structure changes measured by optical coherence tomography, cardiorespiratory fitness) and biological parameters (inflammation, oxidative stress and neurotrophic factors) at baseline, after a four-month intervention period, and six-month follow-up. Discussion: This is an innovative study aimed at gaining a deeper understanding of the physiopathology of BD and determining whether the prognosis and evolution of the disease can be improved through modifiable areas of the patient’s lifestyle. Ethics and Dissemination: This study protocol was approved by the Local Ethics Committee. All participants must sign informed consent prior to being included in the study. The results will be published after completion of the study and presented in national and international conferences. Trial registration: NCT04400630. NCT clinicaltrials.gov. Date of registration in primary registry 22 May 2020. clinicaltrials.gov.